2023
DOI: 10.1249/mss.0000000000003160
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen-Month Changes in Physical Activity, Body Weight, Quadriceps Strength, and Gait Biomechanics during the COVID-19 Pandemic

Abstract: PurposeThis study assessed the effects of the COVID-19 pandemic restrictions/lockdowns on physical activity levels, body mass, quadriceps strength, and gait biomechanics over 18 months.MethodsTen healthy men were assessed at baseline (~14 wk before first lockdown) and 17.9 ± 0.3 months later (<1 wk after second lockdown). At both times, physical activity levels, body mass, and quadriceps strength were acquired using the International Physical Activity Questionnaire, a force plate, and a dynamometer, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The long-term health effects of this period of increased sedentary living have not been established; however, studies are emerging and have identified associated factors that may have health consequences. This study published in the August issue of MSSE , out of Berlin, Germany took advantage of gait biomechanics data collected just prior to the COVID-19 lockdown in Germany to assess changes in weight, physical activity, quadriceps strength, and gait biomechanics during the approximately 15 months of pandemic isolation policies (2).…”
Section: -Month Changes In Physical Activity Body Weight Quadriceps S...mentioning
confidence: 99%
“…The long-term health effects of this period of increased sedentary living have not been established; however, studies are emerging and have identified associated factors that may have health consequences. This study published in the August issue of MSSE , out of Berlin, Germany took advantage of gait biomechanics data collected just prior to the COVID-19 lockdown in Germany to assess changes in weight, physical activity, quadriceps strength, and gait biomechanics during the approximately 15 months of pandemic isolation policies (2).…”
Section: -Month Changes In Physical Activity Body Weight Quadriceps S...mentioning
confidence: 99%